Closing the gap in Australian Aboriginal infant immunisation rates -- the development and review of a pre-call strategy. (December 2016) - Cashman, Patrick; Allan, Natalie; Clark, Katrina; Butler, Michelle; Massey, Peter; Durrheim, David
Abstract Background Improving timely immunisation is key to closing the inequitable gap in immunisation rates between Aboriginal children and non-Indigenous children. Aboriginal Immunisation Officers were employed in Hunter New England Local Health District (HNELHD), New South Wales (NSW), Australia, to telephone the families of all Aboriginal infants prior to the due date for their first scheduled vaccination. Methods Aboriginal Immunisation Officers contacted the families of Aboriginal children born in the Hunter New England Local Health District (HNELHD) by telephone before their due immunisation date (pre-call) to provide the rationale for timely immunisation, and to facilitate contact with culturally safe local immunisation services if this was required. The impact of this strategy on immunisation coverage rates is reviewed. Results For the period March 2010 to September 2014 there was a significant increase in immunisation coverage rate for Aboriginal children at 12 months of age in HNELHD (p  < 0.0001). The coverage in the rest of NSW Aboriginal children also increased but not significantly (p  = 0.218). Over the full study period there was a significant decrease in the immunisation coverage gap between Aboriginal children and non-Indigenous children in HNELHD (p  < 0.0001) and the rest of NSW (p  = 0.004). The immunisation coverage gap between Aboriginal and non-Indigenous infants decreased at a significantly faster rate in HNELHD than the rest of NSW (p  = 0.0001). By the end of the study period in 2014, immunisation coverage in HNELHD Aboriginal infants had surpassed that of non-Indigenous infants by 0.8 %. Conclusions The employment of Aboriginal immunisation officers may be associated with closing of the gap between Aboriginal and non-Indigenous infants' immunisation coverage in HNELHD and NSW. The pre-call telephone strategy provided accelerated benefit in closing this gap in HNELHD.